College math

-3-4(t-5)=-2(t+3)+11

Multipy out the terms in parentheses and then combine the constants. Adding "2t" to both sides will leAave you with -2t on the lest side.
Then solve for t

  1. 👍 0
  2. 👎 0
  3. 👁 109
asked by Alecia

Respond to this Question

First Name

Your Response

Similar Questions

  1. algebra

    3x-5(3x-7)= 2(x+9) + 45 You won't learn unless you try these yourself. Multiply out the term in parentheses, combine the x terms together and the constants together, and then put all the x terms on one side of the = and the

    asked by Anonymous on April 24, 2007
  2. Algebra

    Could someone please help me find x in this problem and explain how you got the answer? 2(3x - 1) = 5 - (x + 3) I checked the answer I got in the back of my algebra book and it said the answer was 4/7 but my answer was wrong. How

    asked by Jamie on August 12, 2006
  3. Maths

    you have to solve the following by finding the value of x and y. can u help please? x+3(x+1)=2x 1+3(x-1)=4 2x-2(x+1)=5x 2(3x-1)=3(x-1) 4(y-1)+3(y+2)=5(y-4) 3y+7+3(y-1)=2(2y+6) These are exercises in standard algebraic manipulation

    asked by number 420 on April 22, 2007
  4. Briittany algebra question

    You should have posted this as a new question, not as a comment to someone else's thread. > Just combine "x" terms and combine constants on separate sides of the equation -x = 2 x = -2 x = -2

    asked by drwls on December 1, 2008
  5. algebra

    Remove the parentheses from the following expression, and combine like terms: (2x + 3y – 4z) – (x – y – z) A. 3x + 4y + 5z B. 3x + 4y – 3z C. x + 4y – 3z D. x + 2y – 5z

    asked by amanda on November 17, 2013
  6. algebra

    Remove the parentheses from the following expression, and combine like terms: 3(ax + b2 – c) + 2

    asked by Anonymous on May 8, 2017
  7. Algebra

    Remove the parentheses from the following expression, and combine like terms: (a + b – c) + 3a – 2c A. 2a – b + c B. 4a + b + 3c C. 4a + b – 3c D. 2a – b – c

    asked by Jen on November 15, 2013
  8. Algebra

    Remove the parentheses from the following expression, and combine like terms: (2x + 3y – 4z) – (x – y – z) A.3x +4y+5z B. 3x + 4y – 3z C.x +4y–3z D. x + 2y – 5z

    asked by L on November 15, 2013
  9. math

    could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17

    asked by Abby on September 17, 2015
  10. math

    could someone check my work please? I have to solve for 'x' Questions ~ 1. 3x – 19 = -2 Add ‘19’ to each side of the equation ~ -19+19+3x= -2+19 Combine like terms~ -19+19=0 0+3x= -2+19 3x= -2+19 Combine like terms~ -2+19=17

    asked by Abby on September 18, 2015

More Similar Questions